Impact of IYCF practices, as measured by national nutrition surveys from 2018 to 2022, on stunting and under-5 survival in Burkina Faso: a LiST analysis - Kere, Natacha; Compaore, Ella W. R.; Keita, Youssouf; Ouedraogo, Daniel S.; Tirogo, Souleymane; Bambara, Estelle A.; Coulibaly, Z. Thierry; Dicko, Mamoudou H. (Frontiers in Nutrition, 2025)
IntroductionBurkina Faso is facing a serious public health problem of chronic malnutrition and mortality in children under the age of 5. To tackle this situation, a number of child nutrition interventions have been implemented. This study aims to assess the impact of these interventions on the nutritional status of children aged 0–5 years between 2018 and 2022.MethodsThis study is a modeling of the impact of changes in the coverage of interventions with known effect sizes, using the LiST (Lives Saved Tool). The interventions used concern infant and young child feeding, the coverage of which was measured by the 2018 to 2022 editions of the NNS conducted in Burkina Faso using the SMART methodology. It covered the national level, the Center region and the Sahel region. Extracted intervention coverage levels were entered into LiST, according to six projections in two scenarios (scenario 1 and 2). The modeling results visualized in LiST were exported to Excel for formatting into tables and/or graphs.ResultsThe measured changes in the levels of infant and young child feeding interventions included in this study led to a reduction in the number of cases of chronic malnutrition in children under 6 months of age in the second scenario projections. However, no cases of chronic malnutrition were prevented among children in the 6–59 month age group under any of the six projections. On the contrary, opportunities to save cases of chronic malnutrition have been missed. These missed opportunities amount to 64,880 in scenario 1 and 39,556 in scenario 2 at national level. Nevertheless, 920 lives were saved nationwide, 232 in the Center region and 202 in the Sahel region.ConclusionThe study highlighted the need to strengthen the implementation of IYCF interventions, coupled with a significant improvement in the quality of NNS data collection, given the up and down nature of the indicators, which makes them difficult to use for decision-making.